1985
DOI: 10.1051/lait:1985647-6482
|View full text |Cite
|
Sign up to set email alerts
|

Influence de la supplémentation du lait en magnésium sur la fermentation lactique réalisée par S. lactis et S. thermophilus

Abstract: 1985 / N°647 better survival rate of lactic streptococci. The study of magnesium distribution in the different proteinic fraction of reconstituted skim milk, using the Sephadex G 50 chromatography method by elution with distilled water, allowed us ta show that magnesium exists in three states: protein-bound (27 ta 30 ppm), peptid-bound (8 ppm) and a free state (64 ppm). Incubation with S. lactis and S. thermophilus transfers the balance of the magnesium distribution observed. One effect of adding magnesium is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In milk, the Mg 2+ concentration varies from 4.2 to 6.25 mM, depending on the geographic region (Veisseyre 1975). Interestingly, supplementation of milk with 1-2.1 mM Mg 2+ permitted both a stimulation of growth of S. thermophilus and S. lactis and a better survival rate of the lactic streptococci (Amouzou et al 1985). Interesting results about antibacterial properties of Mg 2+ were obtained by Duane and coauthors (Robinson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In milk, the Mg 2+ concentration varies from 4.2 to 6.25 mM, depending on the geographic region (Veisseyre 1975). Interestingly, supplementation of milk with 1-2.1 mM Mg 2+ permitted both a stimulation of growth of S. thermophilus and S. lactis and a better survival rate of the lactic streptococci (Amouzou et al 1985). Interesting results about antibacterial properties of Mg 2+ were obtained by Duane and coauthors (Robinson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mn 2+ helps the cell to deal with reactive oxygen species and serves as an alternative for the absence of a gene encoding a superoxide dismutase (Wegkamp et al 2010). Mg 2+ was earlier found to stimulates the growth of Lactobacillus and improve its survival (Amouzou et al 1985). It was shown that Mg 2+ is the only essential oligoelement for the growth of Lactobacillus delbrueckii subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Although milk contains sufficient magnesium for microbial growth, an exogenous surplus (ca. 16–50% of the normal supply in milk) of this mineral stimulated growth of two streptococci 34 . Potassium is another macro-nutrient for microbial cells, because it is involved in many enzyme activities 27 .…”
Section: Discussionmentioning
confidence: 99%